Deep venous thrombosis in the nonoperated leg after primary major lower extremity arthroplasty. Issue 7 (October 2015) - Rong, Zhen; Xu, Zhihong; Sun, Ye; Yao, Yao; Song, Kai; Chen, Dongyang; Shi, Dongquan; Dai, Jin; Zheng, Minghao; Jiang, Qing
<x xml:space="preserve">Abstract</x> Venous thromboembolism (VTE) is a common complication after major orthopedic surgery. However, the reported rates of deep venous thrombosis (DVT) vary widely. Our aim was to study the incidence of DVT in the nonoperated leg after primary major lower extremity arthroplasty using bilateral venography. The records of patients who underwent total hip arthroplasty (THA) or total knee arthroplasty (TKA) at our institution between August 2013 and August 2014 were reviewed. We examined the records for a total of 380 patients, of which 244 had undergone bilateral venography 3–5 days after THA or TKA. A total of 244 patients undergoing TKA (n = 119) or THA (n = 125) were recruited for this study. DVT was diagnosed in 42 (17.2%) of the 244 patients; nine patients developed DVT in both legs, and four developed DVT only in the nonoperated leg. All of the DVTs were located in calf veins. DVT occurred more frequently after TKA than THA, especially in muscular veins. Female sex and older age were found to be positive risk factors for DVT after THA. The incidence of DVT after major lower arthroplasty is high. DVT in nonoperated legs should be carefully considered because of its potential risks, especially in left. Distal DVT also has a high risk to develop pulmonary embolism (PE). The combination of anticoagulant and pneumatic compression is a good measure to avoid proximal DVT, and it is well tolerated to stop anticoagulant if the patients were diagnosed as having no DVT.